Comparison of wound healing of skin incision on albino rat (Rattus norwegicus) by treatment of electrical stimulations - Rina Puspasari Herdiawan; Andri Rezano; . Vitriana; Irma Ruslina; Pritha Pitaloka; . Achadiyani (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
Wound interferes with the equilibrium of skin functions. It disrupts a barrier function of the skin as external barrier of the internal organ from physical, chemical and biological environment. The wound can be easily treated but neglected wound can lead to several complications. Accelerate wound healing will prevent complications and reduce aesthetic problem in anti-aging treatment. Previous studies showed that physical modulation as electrical stimulation could enhance wound healing processes. This study purposed to compare three different modes of electrical stimulation on wound healing such as transcutaneous electrical nerve stimulation (TENS), high voltage pulse current (HVPC) and low-intensity direct current (LIDC). This in vivo study used incisional skin biopsy of albino rat (Rattus norvegicus). Qualitative and quantitative parameters were analyzed to compare three different electrical stimulations on the wound healing response on the epidermis, dermis, inflammation, and angiogenesis phase. The highest histological score on the epidermis and dermis was found on LIDC whereas the highest histological score on the inflammation and angiogenesis phase was found on HVPC. This result of this study may provide useful information for selecting additional treatment for wound healing.